Exploring the lived experiences of Singapore's "opt‐out" mothers: Introducing "Professional Motherhood". Issue 3 (31st January 2022) - Kerrane, Ben; Banister, Emma; Wijaya, Hadi
Abstract: This article explores the experiences of 10 educated middle‐class Singaporean women who act in contrast to the state's neoliberal focus on continuous employment, opting‐out of full‐time professional work to intensively parent their children. Using the theoretical lens of intensive motherhood and a qualitative longitudinal approach, we explore how these women legitimize their position, highlighting a culturally specific performance of motherhood ("Professional Motherhood"). Professional motherhood enrolls elements of former professional identities and skillsets into everyday motherhood, performed through three strategies: positioning, productive, and practicing motherhood. We contribute to existing literature by demonstrating that culturally informed variations of motherhood exist beyond the (largely Western) dominant lens of intensive motherhood ideology. Professional motherhood is experienced as a radical step by women, proving partially successful in legitimizing opt‐out decisions. However, by incorporating and further emphasizing deeply ingrained ideal worker expectations, women risk further upholding the state's competing logics and their obligations as mothers/workers.